The processing of hierarchical nanocomposites - Umer, R.; Li, Y.; Liao, K.; Dong, Yu; Haroosh, Hazim Jasim Mohammed (Elsevier, 2015)
In this chapter, the effects of graphene oxide (GO) nanoparticles on glass fiber composite processing by incorporating them into epoxy resin were investigated. GO was synthesized from graphite powder and was mixed with epoxy resin. Three different GO contents of 0.05, 0.1, and 0.2 wt% were used. Epoxy/GO nanocomposite samples were tested for rheology and cure kinetics to evaluate the effects of GO content on important resin infusion processing parameters. The results show that adding GO to neat epoxy resin increased the viscosity and affected the resin cure reaction by reducing the resin gel time. After that, glass fiber composites were prepared using the resin infusion process. Samples with 0.2 wt% GO result in very slow resin infiltration time with premature resin gelation. Thirty percent increase in flexural strength and 21% increase in flexural modulus are manifested by adding GO as the secondary reinforcement to glass fiber composites.